Lithologically Controlled Subsurface Critical Zone Thickness and Water Storage Capacity Determine Regional Plant Community Composition. Issue 4 (15th April 2019) - Hahm, W. Jesse; Rempe, Daniella M.; Dralle, David N.; Dawson, Todd E.; Lovill, Sky M.; Bryk, Alexander B.; Bish, David L.; Schieber, Juergen; Dietrich, William E.
Abstract: Explanations for distinct adjacent ecosystems that extend across hilly landscapes typically point to differences in climate or land use. Here we document—within a similar climate—how contrasting regional plant communities correlate with distinct underlying lithology and reveal how differences in water storage capacity in the critical zone (CZ) explain this relationship. We present observations of subsurface CZ structure and groundwater dynamics from deep boreholes and quantify catchment‐wide dynamic water storage in two Franciscan rock types of the Northern California Coast Ranges. Our field sites have a Mediterranean climate, where rains are out of phase with solar energy, amplifying the importance of subsurface water storage for periods of peak ecosystem productivity in the dry season. In the deeply weathered (~30 m at ridge) Coastal Belt argillite and sandstone, ample, seasonally replenished rock moisture supports an evergreen forest and groundwater drainage sustains baseflow throughout the summer. In the Central Belt argillite‐matrix mélange, a thin CZ (~3 m at ridge) limits total dynamic water storage capacity (100–200 mm) and rapidly sheds winter rainfall via shallow storm and saturation overland flow, resulting in low plant‐available water (inferred from predawn tree water potential) and negligible groundwater storage that can drain to streams in summer. This storage limitation mechanism explains the presence of an oak savanna‐woodland bounded by seasonally ephemeral streams, despite >1, 800 mm of average precipitation. Through hydrologic monitoring and subsurface characterization, we reveal a mechanism by which differences in rock type result in distinct regionally extensive plant communities under a similar climate. Plain Language Summary: The ability of the subsurface critical zone—extending from the ground surface down to fresh, unweathered bedrock—to store and release water to plants and streams is a key variable explaining ecosystem composition and function. The storage and release of water are particularly important in Mediterranean climates, where rain arrives in winter and summers are typically warm and dry. Here plants rely half the year on seasonally replenished water from belowground. We documented how the subsurface structure of the critical zone determines how water is shed from landscapes and how much water can be seasonally stored. We found that locations with a thicker critical zone had higher water storage capacity, more productive ecosystems, deeper groundwater runoff generation, and greater summer streamflow. Where the critical zone is thin and storage capacity is limited, the subsurface completely saturates, and the landscape sheds incoming rain via surface runoff. This water storage limitation explains the presence of an oak savanna‐woodland in the Northern California Coast Ranges, where rainfall is ample, and neighboring areas experiencing similar climate have towering forest canopies. Rock type governed these variations, highlighting its importance in determining the distribution of ecosystems and water runoff pathways to streams. Key Points: Under a similar climate, adjacent landscapes across an extensive region of the Northern California Coast Ranges are either evergreen forest or deciduous oak savannah Lithology controls the extent of bedrock weathering and water storage capacity and thereby plant‐available moisture in the summer dry season A thick subsurface critical zone supports evergreen forest, whereas an adjacent thin subsurface critical zone sustains savannah